Are you alone wise? : the search for certainty in the early modern era - Schreiner, Susan E. (Susan Elizabeth) (New York : Oxford university Press, 2011)
Susan Schreiner argues that Europe in the 16th century was preoccupied with certainty, especially religious certainty. She analyzes the pervading questions about certitude & doubt in the terms & contexts of a wide variety of thinkers during this time of competing truths.
Certainty: a contemporary question -- Beginnings: questions and debates in the fourteenth and fifteenth centuries -- Abba Father: the certainty of salvation -- The spiritual man judges all things: the certainty of exegetical authority -- Are you alone wise?: the Catholic response -- Experientia: the great age of the Spirit -- Unmasking the angel of light: the discernment of the spirits -- Men should be what they seem: appearances and reality.
First issued as an Oxford University Press paperback 2012.
Keywords: Certainty; Church history -- Middle Ages, 600-1500.; Church history -- Modern period, 1500-; Philosophy, Modern; Philosophy, Renaissance; filosofia; renessanssi; varmuus; filosofi; renässansen; förvissning